4‐3: Distinguished Paper: IGZO TFT Arrays for Biometrics‐Under‐Display and Biomedical Applications. Issue 1 (28th June 2021) - Kronemeijer, Auke Jisk; de Haas, Gerard; Verbeek, Roy; Bel, Thijs; van de Laar, Robert; Ugalde-Lopez, Leslye; Gelinck, Gerwin
Abstract : This paper presents a monolithic manufacturing process to realize active‐matrix meshed TFT arrays on foil with physical voids between pixels, realizing membrane‐like structures for use in biometrics‐under‐display applications. Moreover, however, the concept enables new applications in the biomedical electronics domain.